Peripheral neuropathy secondary to traction injury resulting from the use of physical restraints - Sahathevan, Ramesh; Hamidon, Basri; Maniam, Thambu; Azman Ali, Raymond (ASEAN Neurological Association, 2010)
We describe the case of a 46 year-old woman who developed weakness of the upper limbs while admitted for relapsed chronic schizophrenia. She was combative, necessitating the use of physical restraints in the form of wrist bands that were used to secure her to the bed frame. In addition, she was treated with haloperidol and benzhexol. Her physical findings were consistent with a lower motor neuron injury confined to the upper limbs and a nerve conduction study confirmed a mixed demyelinating axonal injury resulting in a predominantly motor neuropathy. She made an almost complete recovery by 6 months. We suggest that her condition was due to neuropraxia secondary to traction injury affecting the brachial plexus as an indirect consequence of the use of physical restraints.